Anatomical Variations of the Anterior Clinoid Process: A Study of 597 Skull Base Computerized Tomography Scans. Issue 3 (September 2016) - da Costa, Marcos Devanir Silva; de Oliveira Santos, Bruno Fernandes; de Araujo Paz, Daniel; Rodrigues, Thiago Pereira; Abdala, Nitamar; Centeno, Ricardo Silva; Cavalheiro, Sergio; Lawton, Michael T.; Chaddad-Neto, Feres
Abstract : BACKGROUND: The anterior clinoid process (ACP) is surrounded by a complex anatomy; variations include pneumatization and the formation of bone bridges with the middle and posterior clinoid, which complicate surgery. The key to avoiding microsurgical complications is a perfect understanding of this anatomy. OBJECTIVE: To explore the anatomic variations of the ACP. METHODS: Between January 1, 2013, and September 6, 2014, 597 skull base computed tomography scans were performed to evaluate inner ear disease in patients with no history of paranasal sinus disease or endonasal surgery. The base width and length of the ACP, complete carotid-clinoid foramen and sella turcica bridge, and sphenoid sinus pneumatization volume were assessed. ACP pneumatization was assessed with the use of a novel classification system. RESULTS: The scans were derived from a population of 343 female patients (57.5%), with a mean age of 38.6 years (0.2-90 years). ACP base width and length were 7.7 ± 1.73 and 10.31 ± 2.1 mm, respectively. Anatomic variations were present in 38.7% of scans. ACP pneumatization was present in 25.5% of scans, and carotid-clinoid foramen and sella turcica bridge were present in 14.2% and 14.4% of scans, respectively. There was no pneumatization of the ACP in patients <10 years of age and no progression of the pneumatization of the sphenoid sinus in patients >10 years old. CONCLUSION: At least 1 variation in ACP anatomy was found in 38.7% of cases with this simple method. Thus, a preoperative computed tomography scan could improve surgical procedures that involve removal of the anterior clinoid process. ABBREVIATIONS: ACP, anterior clinoid process CCF, carotid-clinoid foramen ICA, internal carotid artery STB, sella turcica bridge